Inventaire Des Champignons Pathogènes Post-Récolte De La Banane Dessert « Cavendish » Et Evaluation De Leur Sensibilité A l’Azoxystrobine En Côte d’Ivoire - Kouadio, Kouakou Théodore; Agneroh, Thérèse Atcham; Pohé, Jean; Tienebo, Eric-Olivier; Ohoussou, N'sou Isis Lucie Victoire (European Scientific Journal, ESJ, 2017)
This study was aimed at drawing up an inventory of the post-harvest pathogenic fungi of banana dessert and to assess their susceptibility to Azoxystrobin. A sampling was carried out in banana fruit processing factories of the main Ivorian zones of banana production (Niéky, AboissoAyamé-Akressi and Tiassalé). The identification and frequency of isolation of the fungal species associated with the affected parts of the fruit was based on their cultural aspects, reproductive structures and percentage of contamination. The susceptibility of post-harvest fungi to different doses of Azoxystrobin 3.5, 4 and 4.5 g/hl was compared to a reference product, Bitertanol at a dose of 2 g/hl and to a check where only water is applied. Of the 13 pathogenic fungal species isolated, Botryodiplodia theobromae was the most recurrent and was identified as the main causal agent of postharvest rots. It is followed by Colletotrichum musae, Aspergillus niger, Fusarium moniliforme, Geotrichum candidum, Fusarium semitectum and Aspergillus flavus, in which the isolation frequencies are significantly different. The results on the susceptibility of pathogenic fungi to Azoxystrobin show that the three doses of Azoxystrobin have significantly different effects from that of the reference product and the check. They reduce infection rates up to 91.67% and give a high proportion of marketable fruits, respectively. Surprisingly, the dose of the reference product gives a low rate of reduction of infections (49%) and a proportion of marketable fruit that is significantly identical to that of water treatment.